Membrane bioreactor for domestic wastewater treatment: principles, challanges and future research directions - Muhammad Roil Bilad (Indonesian Journal of Science and Technology, 2017)
Membrane bioreactors (MBRs) have recently become widely accepted as an advanced technology for treatment of domestic and industrial wastewaters. The objective of this review is to provide overview on MBR technology for wastewater treatment application. It includes discussions on the fundamental, core problems (membrane fouling), recent effective development approach (dynamic filtration systems) and future research direction of MBRs. Since MBRs integrate a conventional activated sludge process with membrane filtration, and both fundamental aspects are discussed first. Later, a comprehensive discussion about membrane fouling, the main problems in MBR, is provided, including fouling control strategies. The discussion on the MBR membranes and relation between membrane properties and MBR performance is also provided. This review also includes one of the most promising MBR technologies that specifically design to manage membrane fouling: dynamic filtration systems. Lastly, insight into an approach to address MBRs challenges and recent research and developments are provided.